Sensitivity of Parents in Dealing with Children's Association in Mangun Jaya Share, Kayuagung District - Azizah Husin; Mega Junita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine parents' sensitivity in dealing with children's interactions with indicators of attention, care, control, and supervision. This study used the descriptive qualitative method. This research is located in Neighborhood I, Mangun Jaya Village, Kayuagung District. The subjects of this study amounted to five people, namely parents of children who play gambling. Data collection techniques in this study used interviews and observation. Data analysis techniques used are data collection, data reduction, data presentation, and conclusion. The results showed that parents did not have sensitivity in controlling concerns, where parents gave freedom to children to play outside the home. Parents did not have sensitivity in supervising children playing, and parents did not see or know what children were doing when playing or playing outside. Parents have sensitivity in the form of attention to children playing, and parents have sensitivity in parental care for children's education. For this reason, it is recommended that parents increase awareness of sensitivity always to give attention, care, control and supervision of children playing, especially in controlling and supervising children when playing.